PARTISIPASI ANGGOTA PADA KEGIATAN KELOMPOK TANI MITRA JAYA DI DESA MUNDUNG KECAMATAN TOMBATU TIMUR - Cindy Kartika Tulandi; Celcius ., Talumingan; Sherly Gladys Jocom (Sam Ratulangi University, 2018)
This study aims to determine the participation of members in the Mitra Jaya farmer group activities in Mundung Village, East Tombatu District. This research took place from October to December 2018. The data used were primary data obtained through interviews using a questionnaire to10 respondents and secondary data obtained from the Mundung Village Office in East Tombatu District. The technique of collecting data uses census techniques. Data analysis used in this study is descriptiveanalysis using a Likert Scale. The results showed that the participation of members in farmer groups was high, because they participated in each activity held by the Mitra Jaya farmer groups both in the activities of the planning stage, the implementation stage and the evaluation phase of farmer group activities. The participation of members in the Mitra Jaya farmer group in Mundung Village, Tombatu Timur District in the management of farmer group activities is high.*eprm*.